Efficient recyclable photocatalyst for suzuki coupling reaction and catalytic composite membrane, preparation method and application

CN122912898APending Publication Date: 2026-10-16ZHEJIANG SCI-TECH UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611197231.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

[0007]针对现有铃木偶联光催化剂存在载体比表面积较低、光吸收及光生电荷分离传输能力较弱、Pd活性位点分散性差且缺乏电子结构调控,导致催化活性低、稳定性欠佳等核心技术问题,本发明通过优化前驱体组分与合成溶剂体系,可控制备得到铜单原子掺杂的花状中空球形石墨相氮化碳载体,并采用光沉积策略在氮化碳表面的铜单原子位点上构筑高分散、可电子调制的Pd活性中心,有效实现载体与Pd活性位点的界面电子调控,大幅提升Pd原子利用率与催化反应动力学性能,成功制备出一种兼具高催化效率与长循环使用寿命的新型铃木偶联光催化剂

Benefits of technology

[0022] 1. The catalyst of this invention consists of palladium clusters supported on copper-doped flower-shaped hollow spherical graphitic carbon nitride. This support is prepared by pyrolysis of melamine and cyanuric acid after supramolecular self-assembly to complex copper ions. By controlling the precursor morphology through solvent polarity, the adsorption capacity and light absorption capacity of the reactants are improved, effectively promoting the Suzuki coupling reaction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122912898A_ABST
    Figure CN122912898A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of heterogeneous nanocatalyst, and particularly relates to a high-efficiency recyclable Suzuki coupling reaction photocatalyst and a catalytic composite film, a preparation method and application, the present application constructs a copper monatomic precise regulation and control Pd active site cluster flower-shaped hollow graphite phase carbon nitride visible light catalytic system Pd / CuCN-DMSO; first, melamine and cyanuric acid are used as raw materials to self-assemble and complex copper ions in a dimethyl sulfoxide solvent medium, and a copper monatomic doped flower-shaped hollow carbon nitride carrier is obtained by high-temperature calcination, then the palladium cluster is directionally loaded on the copper monatomic site through photodeposition, and the electronic structure of the palladium active center is optimized by means of copper monatomic electron regulation. The powder catalyst is blended with polyvinylidene fluoride, and a catalytic composite film is prepared through non-solvent induced phase separation. The catalyst can efficiently catalyze Suzuki coupling under visible light driving, and the activity is stable after recycling; the composite film has the advantages of high catalytic activity and easy separation, and can be recycled for multiple times, thereby improving the industrial application potential of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of heterogeneous nanocatalyst technology, and in particular to a highly efficient and recyclable Suzuki coupling reaction photocatalyst and catalytic composite membrane, preparation method and application. Background Technology

[0002] Palladium (Pd)-catalyzed Suzuki coupling reactions have become a core reaction for synthesizing high-end fine organic chemicals such as polyolefins, styrene, and biphenyl derivatives due to their advantages such as mild reaction conditions, wide substrate applicability, and strong functional group tolerance. They are widely used in pharmaceutical intermediates, functional materials, and fine chemicals. Traditional homogeneous catalysts based on Pd complexes (such as palladium-triphenylphosphine complexes) are currently the mainstream catalytic system for Suzuki coupling reactions due to their high catalytic activity and good product selectivity. However, homogeneous catalytic systems have several inherent drawbacks: firstly, the homogeneous catalyst is completely miscible with the reaction system, making it difficult to separate and recover the precious metal palladium. This not only wastes precious metal resources and increases production costs but also easily leads to trace palladium residues in the product, affecting product purity; secondly, the organic ligands used in homogeneous catalysts have complex synthesis processes, high preparation costs, and biotoxicity, affecting the overall greenness and economic efficiency of the process.

[0003] To overcome the aforementioned drawbacks of homogeneous catalytic systems, constructing heterogeneous catalytic systems by loading active Pd species onto the surface of solid supports has become an important approach to improve catalyst recyclability and process economy. Currently, most heterogeneous Suzuki coupling catalysts are prepared by loading palladium nanoparticles onto supports such as metal oxides, carbon materials, and molecular sieves. While this effectively solves the problem of difficult recovery of homogeneous catalysts, significant technical shortcomings remain: these catalytic systems rely on external heating to drive the reaction, resulting in high energy consumption. Furthermore, they are prone to leaching and shedding of active palladium species, inducing side reactions in substrate functional groups. This not only reduces the atom economy of the reaction but also shortens the catalyst's lifespan, making it difficult to meet the demands of high-efficiency industrial production in terms of overall catalytic performance.

[0004] Compared to traditional thermocatalysis, solar-driven heterogeneous Suzuki coupling photocatalysis is a novel, green, and low-carbon catalytic technology. Photocatalysis leverages photogenerated carriers generated by photoexcitation on a semiconductor support to accelerate key elementary reaction steps in the Suzuki coupling reaction, such as oxidative addition, transmetalation, and reductive elimination, achieving highly efficient coupling reactions at room temperature. This fundamentally reduces reaction energy consumption and suppresses high-temperature side reactions. However, current heterogeneous palladium-based photocatalysts still suffer from limitations in support design, uneven Pd active site loading, and weak interactions between Pd and the support, leading to significant problems such as low Pd atom utilization, poor catalytic performance, and poor recyclability. Therefore, it is necessary to combine support design with Pd active site optimization to develop greener, more efficient, and lower-cost heterogeneous photocatalysts.

[0005] In addition, existing heterogeneous powder catalysts exhibit high dispersion in liquid-phase reaction systems, making rapid and complete separation from the liquid phase after the reaction difficult. This not only leads to catalyst loss but also increases the complexity and cost of product separation and purification, hindering the industrial application of this type of catalytic technology. Preparing a catalytic composite membrane by combining powder catalysts with a polymer matrix can effectively solve the problem of powder catalyst separation. While retaining excellent catalytic activity, it endows the catalyst with a macroscopically regular membrane structure, allowing for rapid recovery and reuse through simple clamping or filtration. This simplifies the operation process and improves the reusability of the catalyst. However, this composite membrane catalytic system has not yet been applied to high-performance Suzuki coupling catalysis scenarios.

[0006] In summary, existing Suzuki coupling reaction catalytic technologies generally suffer from a series of problems, including high catalyst cost, low Pd atom utilization, limited catalytic efficiency, difficulties in separation and recovery, short cycle life, and high reaction energy consumption. Therefore, targeted optimization of Pd active sites, improvement of support structure, construction of novel composite catalytic systems, and development of new green, environmentally friendly, low-energy-consumption, highly efficient, stable, and recyclable catalytic materials and technologies are of significant research value and practical application prospects for promoting the green and efficient industrialization of Suzuki coupling reactions. Summary of the Invention

[0007] To address the core technical problems of existing Suzuki coupling photocatalysts, such as low specific surface area of ​​the support, weak light absorption and photogenerated charge separation and transport capabilities, poor dispersion of Pd active sites, and lack of electronic structure regulation, resulting in low catalytic activity and poor stability, this invention optimizes the precursor composition and synthesis solvent system to controllably prepare copper-doped flower-shaped hollow spherical graphitic carbon nitride supports. A photodeposition strategy is then employed to construct highly dispersed, electronically modulated Pd active centers on the copper single-atom sites on the carbon nitride surface, effectively achieving interfacial electronic regulation between the support and Pd active sites. This significantly improves Pd atom utilization and catalytic reaction kinetics, successfully preparing a novel Suzuki coupling photocatalyst with both high catalytic efficiency and long cycle life. This catalyst consists of Pd clusters uniformly supported on copper-doped graphitic carbon nitride supports, where the mass fraction of Pd is adjustable within the range of 0.1–2.0 wt.%. Meanwhile, addressing the shortcomings of traditional powder photocatalysts, such as easy loss, cumbersome separation and recovery, and poor reusability, this invention further combines the aforementioned modified powder catalyst with a polyvinylidene fluoride (PVDF) substrate to prepare an integrated catalytic composite membrane. This catalytic composite membrane has controllable thickness and its area can be flexibly adjusted according to actual reaction equipment and production needs. It can stably and efficiently catalyze the Suzuki coupling reaction, possessing both excellent catalytic performance and the advantages of macroscopic processability and easy recovery in engineering applications.

[0008] To achieve the above-mentioned technical objectives and effects, the present invention is implemented through the following technical solution:

[0009] This invention provides a highly efficient and recyclable photocatalyst for the Suzuki coupling reaction. The photocatalyst is a composite structure in which palladium clusters are supported on copper single-atom-doped flower-shaped hollow spherical graphitic carbon nitride. The copper single-atom-doped flower-shaped hollow spherical graphitic carbon nitride is prepared by supramolecular self-assembly combined with high-temperature calcination using melamine and cyanuric acid as precursors in a dimethyl sulfoxide solvent system, and possesses a multi-level flower-shaped hollow spherical structure. The palladium clusters are directionally supported on the copper single-atom active sites by photodeposition to achieve electronic structure modulation, adapting to the photocatalytic Suzuki coupling reaction.

[0010] Furthermore, the mass fraction of palladium in the photocatalyst is 0.1–2.0 wt.%.

[0011] The present invention also provides a photocatalyst-based catalytic composite membrane, wherein the catalytic composite membrane uses polyvinylidene fluoride as a matrix, is doped and dispersed with the Pd / CuCN-DMSO photocatalyst, and polyvinylpyrrolidone is added as a film-forming aid; the catalytic composite membrane is prepared by a solvent-inducible phase separation method, and has a macroscopic membrane structure, which can be directly clamped, separated and recovered.

[0012] Furthermore, the thickness of the catalytic composite membrane is 100–400 μm, and the membrane area can be adjusted as needed.

[0013] This invention also provides a method for preparing a highly efficient and recyclable Suzuki coupling reaction photocatalyst, comprising the following steps:

[0014] 1) Preparation of copper-doped flower-shaped hollow spherical graphitic carbon nitride support CuCN-DMSO: Melamine and copper-containing raw materials were dissolved sequentially in dimethyl sulfoxide and stirred at room temperature to obtain a homogeneous mixed solution; cyanuric acid was dissolved in dimethyl sulfoxide to obtain a homogeneous solution; the two solutions were mixed and supramolecular self-assembled to obtain a suspension, which was then stirred at room temperature, centrifuged, dried, ground, calcined at high temperature under an inert atmosphere, and cooled to obtain the CuCN-DMSO support;

[0015] 2) Preparation of catalyst by photodeposition of supported palladium: CuCN-DMSO support was dispersed in a pure water system, ultrasonically dispersed and then a soluble palladium salt solution was added. The mixture was pretreated by stirring under dark conditions, and then palladium clusters were deposited by photodeposition. After centrifugation, washing and vacuum drying, Pd / CuCN-DMSO photocatalyst was obtained.

[0016] Further, in step 1), the mass ratio of melamine to dimethyl sulfoxide is 1–10:200, the mass ratio of cyanuric acid to dimethyl sulfoxide is 1–10:200, and the concentration of copper in the mixed solution is 0.258–2.58 g·L⁻¹. -1The calcination temperature is 500–600 °C, the calcination time is 3–5 h, and the calcination atmosphere is nitrogen; in step 2), the mass ratio of CuCN-DMSO to water is 0.5–2:1000, and the palladium concentration in the palladium salt solution is 0.532–2.128 g·L⁻¹. -1 The dark stirring time is 1–4 h, and the light deposition time is 0.5–2 h.

[0017] The present invention also provides a method for preparing the catalytic composite membrane, comprising the following steps: dispersing the prepared Pd / CuCN-DMSO photocatalyst in N,N-dimethylformamide, and ultrasonically dispersing it uniformly to obtain a catalyst suspension; adding polyvinylidene fluoride and polyvinylpyrrolidone to the suspension, and stirring at a constant temperature of 55-85 °C for 2-8 h to prepare a uniform casting solution; uniformly coating the casting solution onto the surface of a substrate, and curing it into a film by a non-solvent-induced phase separation method to obtain a Pd / CuCN-DMSO@PVDF catalytic composite membrane.

[0018] Furthermore, the mass ratio of polyvinylidene fluoride, polyvinylpyrrolidone, N,N-dimethylformamide, and Pd / CuCN-DMSO photocatalyst in the casting solution is 34:10:189.6-303.4:2-12; the polyvinylpyrrolidone is of type K88-96.

[0019] The present invention also provides an application in which a photocatalyst and a catalytic composite membrane are used in a photocatalytic Suzuki coupling reaction.

[0020] Furthermore, the substrates for the Suzuki coupling reaction include halogenated benzenes with different substituents and substituted phenylboronic acid derivatives. The reaction is carried out under ambient temperature and light conditions, and the photocatalyst and catalytic composite membrane can be recycled and reused multiple times.

[0021] The beneficial effects of this invention are:

[0022] 1. The catalyst of this invention consists of palladium clusters supported on copper-doped flower-shaped hollow spherical graphitic carbon nitride. This support is prepared by pyrolysis of melamine and cyanuric acid after supramolecular self-assembly to complex copper ions. By controlling the precursor morphology through solvent polarity, the adsorption capacity and light absorption capacity of the reactants are improved, effectively promoting the Suzuki coupling reaction.

[0023] 2. By utilizing the photogenerated electron capability of carbon nitride and the electron enrichment capability of copper, palladium is directionally induced to deposit on copper sites, resulting in high palladium dispersion. The synthesis process is simple, environmentally friendly, and has the potential for large-scale production. The bimetallic structure formed by palladium and copper can effectively regulate the electronic structure of palladium, reduce the reaction energy barrier, and improve the reaction efficiency.

[0024] 3. The catalyst of this invention exhibits highly efficient photocatalytic Suzuki coupling performance even under mild conditions. When using iodobenzene as a substrate, the Pd (0.5 wt.%) / CuCN-DMSO catalyst achieves a photocatalytic yield of 97.27% after two hours, which is significantly superior to Pd-modified copper single-atom doped bulk carbon nitride (yield 14.9%), copper single-atom doped bubble carbon nitride (yield 74.4%), and copper-free flower-shaped hollow spherical graphitic carbon nitride catalyst (yield 76.4%).

[0025] 4. The composite membrane of this invention has broad and efficient catalytic performance for a variety of reaction substrates (such as bromobenzene, 4-methyliodobenzene, 4-cyanoiodobenzene, 4-hydroxyiodobenzene, etc.), and is widely applicable.

[0026] 5. The composite membrane prepared by the present invention through blending and non-solvent-induced phase separation method allows the catalyst to be uniformly distributed in the PVDF matrix, and has both excellent reactant adsorption capacity and photocatalytic performance; the composite membrane preparation process is simple, the equipment requirements are low, the catalyst is easy to recover, and it is suitable for industrial production.

[0027] Of course, any product implementing this invention does not necessarily need to achieve all of the above advantages at the same time. Attached Figure Description

[0028] To more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0029] Figure 1 These are scanning electron microscope (SEM) images of the catalysts prepared in Example 1 and Comparative Examples 1-3;

[0030] Figure 2 These are the X-ray diffraction (XRD) patterns of the catalysts prepared in Example 1 and Comparative Examples 1-3;

[0031] Figure 3 These are the N2 adsorption-desorption isotherms and pore size distribution diagrams of copper-doped carbon nitride prepared in Example 1 and Comparative Example 3.

[0032] Figure 4 These are the UV-Vis diffuse reflectance (UV-vis DRS) absorption spectra of the carbon nitride, copper-doped carbon nitride, and catalyst prepared in Example 1, and the copper-doped carbon nitride prepared in Comparative Examples 1-3.

[0033] Figure 5 These are SEM images and physical optical photographs of the catalytic composite membrane prepared in Example 1;

[0034] Figure 6 The images show the XRD patterns of the catalyst and catalytic composite membrane prepared in Example 1 and the pure PVDF membrane prepared in Comparative Example 4.

[0035] Figure 7 These are X-ray photoelectron spectroscopy (XPS) spectra of carbon nitride, copper-doped carbon nitride, and catalyst prepared in Example 1 and Comparative Example 1.

[0036] (a) is a C 1s orbital, (b) is an N 1s orbital, (c) is a Cu 2p orbital, and (d) is a Pd 3d orbital;

[0037] Figure 8 These are TOF plots of the 15-minute reaction turnover frequency of the catalysts prepared in Examples 1-4;

[0038] Figure 9 The graph shows the performance of the carbon nitride and catalyst prepared in Example 1 and the catalysts prepared in Comparative Examples 1-4 in catalyzing Suzuki coupling under the same conditions.

[0039] Figure 10 The photocatalytic yields of the catalyst prepared in Example 1 for various reaction substrates are shown.

[0040] Figure 11 This refers to the multiple cycle performance of the catalyst prepared in Example 1;

[0041] Figure 12 These are performance comparison graphs of the catalytic composite membranes prepared in Examples 1, 5, and 6 during multiple cycles of use;

[0042] Figure 13 These are photographs of the catalytic composite membranes prepared in Examples 1, 5, and 6 after several cycles.

[0043] Figure 14 This is a comparison chart of the multiple cycle performance of the catalyst and catalytic composite membrane prepared in Example 1. Detailed Implementation

[0044] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0045] This invention provides a highly efficient and recyclable photocatalyst for the Suzuki coupling reaction and its catalytic composite membrane for the synthesis and application in catalytic Suzuki coupling reactions. A highly dispersed and electronically modulated supported palladium catalyst is synthesized by pyrolyzing melamine and cyanuric acid precursors that form a self-assembled complex with copper ions, followed by photodeposition to support palladium. The catalyst synthesis process is simple, requires low palladium dosage, and exhibits high dispersion. This catalyst demonstrates broad and efficient catalytic performance for various substrates in Suzuki coupling reactions, showing wide applicability and significant application potential. A Pd / CuCN-DMSO@PVDF composite membrane is prepared using a blending-nonsolvent-induced phase separation method, in which the Pd / CuCN-DMSO catalyst is uniformly distributed within the PVDF matrix. The composite membrane possesses excellent reactant adsorption performance and recyclability. This composite membrane effectively solves the problems of difficult recovery and secondary pollution associated with powdered catalysts, making it suitable for industrial production.

[0046] The specific embodiments of the present invention are as follows:

[0047] Example 1

[0048] 1) Synthesis of CuCN-DMSO: 300 mg of melamine was dissolved in 10 mL of dimethyl sulfoxide, and then 20 mg of copper nitrate trihydrate was added. The mixture was stirred at room temperature to form a homogeneous solution. 300 mg of cyanuric acid was dissolved in 10 mL of dimethyl sulfoxide and stirred at room temperature to form another homogeneous solution. The two solutions were mixed and supramolecularly self-assembled to obtain a suspension. The suspension was stirred continuously at room temperature for a certain period of time. After centrifugation, the suspension was washed with water and ethanol and dried under vacuum to obtain a solid powder. The solid powder was thoroughly ground, placed in a covered crucible, and calcined at 550 °C under a nitrogen atmosphere for 4 h. After cooling to room temperature, it was ground thoroughly again to obtain copper single-atom doped carbon nitride material, denoted as CuCN-DMSO.

[0049] 2) Photodeposition of Pd catalyst: 20 mg CuCN-DMSO was dispersed in 20 mL of water and sonicated to ensure uniform dispersion; then 94 μL of 0.01 M ammonium chloropalladate solution was added, and the mixture was stirred in the dark for 2 h, irradiated under 365 nm single-band ultraviolet light for 1 h, centrifuged, washed with deionized water, vacuum dried and thoroughly ground to obtain the catalyst, denoted as Pd(0.5 wt.%) / CuCN-DMSO;

[0050] 3) Preparation of Pd (0.5 wt.%) / CuCN-DMSO@PVDF catalytic composite membrane: 50 mg Pd (0.5 wt.%) / CuCN-DMSO was dispersed in 2 mL N,N-dimethylformamide and sonicated to ensure uniform dispersion; then 400 mg PVDF and 100 mg PVP (K88-96) were added, and the mixture was stirred at 65 ℃ for 5 h to obtain a casting solution; the casting solution was coated onto a glass plate, uniformly coated with a doctor blade, and allowed to stand at room temperature for 12 min. Then, it was placed in deionized water, and the composite membrane was prepared by a solvent-inducible phase separation method. The membrane thickness was 200 μm, and the effective area of ​​the membrane was 16 cm². 2 It is denoted as Pd(0.5 wt.%) / CuCN-DMSO@PVDF-200 μm.

[0051] Example 2

[0052] The difference between this embodiment and Example 1 is that the amount of 0.01 M soluble palladium salt solution in step 2) is changed to 19 μL, and the resulting catalyst is denoted as Pd(0.1 wt.%) / CuCN-DMSO.

[0053] Example 3

[0054] The difference between this embodiment and Example 1 is that the amount of 0.01 M soluble palladium salt solution in step 2) is changed to 57 μL, and the resulting catalyst is denoted as Pd(0.3 wt.%) / CuCN-DMSO.

[0055] Example 4

[0056] The difference between this embodiment and Example 1 is that the amount of 0.01 M soluble palladium salt solution in step 2) is changed to 132 μL, and the resulting catalyst is denoted as Pd(0.7 wt.%) / CuCN-DMSO.

[0057] Example 5

[0058] The difference between this embodiment and Example 1 is that the film thickness in step 3) is changed to 100 μm, and the resulting catalyst film is denoted as Pd(0.5 wt.%) / CuCN-DMSO@PVDF-100 μm.

[0059] Example 6

[0060] The difference between this embodiment and Example 1 is that the film thickness in step 3) is changed to 300 μm, and the resulting catalyst film is denoted as Pd(0.5 wt.%) / CuCN-DMSO@PVDF-300 μm.

[0061] Comparative Example 1

[0062] The difference between this comparative example and Example 1 is that the amount of copper nitrate trihydrate in step 1) is changed to 0 mg, the resulting flower-shaped hollow spherical graphitic carbon nitride is denoted as CN-DMSO, and the catalyst obtained in step 2) is denoted as Pd(0.5 wt.%) / CN-DMSO.

[0063] Comparative Example 2

[0064] The difference between this comparative example and Example 1 is that the solid powder preparation method described in step 1) is changed to: weighing 600 mg of melamine and dispersing it in 20 mL of deionized water, stirring at 80 °C to dissolve it, adding 20 mg of copper nitrate trihydrate, stirring and evaporating at 80 °C to dryness, and the resulting copper single-atom doped blocky carbon nitride is denoted as CuBCN, and the catalyst obtained in step 2) is denoted as Pd(0.5 wt.%) / CuBCN.

[0065] Comparative Example 3

[0066] The difference between this comparative example and Example 1 is that the dissolution conditions of melamine and cyanuric acid in step 1) are changed to dissolution in 10 mL of deionized water at 80 °C. The resulting copper single-atom doped bubble carbon nitride is denoted as CuCN-H2O, and the catalyst obtained in step 2) is denoted as Pd(0.5 wt.%) / CuCN-H2O.

[0067] Comparative Example 4

[0068] The difference between this embodiment and Example 1 is that the amount of Pd (0.5 wt.%) / CuCN-DMSO in the casting solution in step 3) is changed to 0 mg, and the resulting catalyst film is denoted as PVDF-200 μm.

[0069] Figure 1 SEM images of the catalysts prepared in Example 1 and Comparative Examples 1-3 are shown. (a) and (b) exhibit a flower-like hollow spherical morphology; (c) shows a typical blocky carbon nitride morphology; and (d) shows a bubble-like morphology. Characterization results indicate that, compared to the blocky carbon nitride obtained by calcining pure melamine precursor, the melamine-cyanuric acid self-assembled precursor yields a morphology with a larger specific surface area after calcination. Different solvents affect the self-assembly behavior of melamine and cyanuric acid, thereby enabling the control of the carbon nitride morphology.

[0070] according to Figure 2 The XRD patterns of the catalysts prepared in Example 1 and Comparative Examples 1-3 show that each sample exhibits (100) and (002) diffraction peaks of carbon nitride at 13.2° and 27.8°, respectively, proving the successful synthesis of carbon nitride. No diffraction peaks of copper or palladium species were observed in any of the samples, indicating that the metal species are highly dispersed.

[0071] according to Figure 3 The N2 adsorption-desorption isotherms and pore size distribution diagrams of copper-doped carbon nitride prepared in Example 1 and Comparative Example 3 show that both synthesized copper-doped carbon nitrides exhibit type IV isotherm characteristics, proving their mesoporous structure. The specific surface area of ​​CuCN-DMSO was calculated using the formula to be 87.06 m². 2 / g, greater than 81.38 m of CuCN-H2O. 2 / g, confirming the effect of solvent on morphology and specific surface area.

[0072] according to Figure 4 The UV-Vis diffuse reflectance absorption spectra of carbon nitride, copper-doped carbon nitride, and catalyst prepared in Example 1, and copper-doped carbon nitride prepared in Comparative Examples 1-3, show that, compared with different morphologies, copper single-atom-doped flower-shaped hollow spherical carbon nitride exhibits stronger light absorption capacity than bubble-shaped carbon nitride due to its rich pore structure. Compared with and without copper single-atom doping, copper single-atom doping introduces doping energy levels in carbon nitride, enhancing the visible light absorption capacity of the sample. The absorbance in the visible light region is further improved after palladium loading.

[0073] Figure 5 The image shows an SEM image of the catalytic composite membrane prepared in Example 1. The structural features of the Pd (0.5 wt.%) / CuCN-DMSO catalyst can be seen in the pores of the membrane, proving that a blend structure of PVDF and powder catalyst was successfully formed.

[0074] Figure 6 The XRD patterns of the catalyst and catalytic composite membrane prepared in Example 1 and the membrane prepared in Comparative Example 4 are shown. It can be seen that the XRD curve of Example 1 shows both the characteristic peaks belonging to β-PVDF and the characteristic peaks belonging to the carbon nitride (002) crystal plane, which proves the successful synthesis of the catalytic composite membrane.

[0075] according to Figure 7The XPS fine spectra of carbon nitride, copper-doped carbon nitride, and catalyst prepared in Example 1 and Comparative Example 1 show that the binding energies corresponding to N=C−N and C=N−C in the C 1s and N 1s spectra shift to higher binding energies after doping with copper single atoms and loading palladium, indicating electron transfer from the carbon nitride framework to the metal species. The presence of metal-nitrogen bonds in the N 1s spectrum with a lower binding energy shift indicates that nitrogen coordinates with the metal and acts as an electron transport channel. In the Cu 2p spectrum, the binding energy of copper is higher after palladium loading than that of CuCN-DMSO, indicating electron transfer from copper to palladium. Comparing the binding energy of Pd 3d with and without copper, palladium in Pd / CuCN-DMSO is more electron-rich, confirming the effective modulation of the palladium electronic structure by copper. In the Suzuki coupling reaction, electron-rich palladium sites favor the forward direction of the rate-determining oxidative addition step; therefore, copper single-atom doping enhances the electron supply to palladium, thereby improving the coupling efficiency.

[0076] Specific applications of this invention are as follows:

[0077] Application Example 1

[0078] The experimental procedures for the photocatalytic Suzuki coupling reaction of the various catalysts prepared in this invention are as follows:

[0079] 1) Disperse 0.5 mmol halobenzene, 0.6 mmol phenylboronic acid or phenylboronic acid derivative, 1.2 mmol anhydrous potassium carbonate, and 3 mg catalyst in a quartz reaction tube containing 4 mL solvent (2 mL water + 2 mL ethanol) to form a suspension.

[0080] 2) A 300 W Xe lamp was used as the light source, providing visible light with a wavelength range mainly between 400-800 nm. The maximum light power density irradiating the surface of the reaction solution was 200 mW·cm². −2 To carry out photocatalytic reactions.

[0081] 3) After the reaction, dichloromethane was used for extraction, and the remaining reactants and products were quantitatively analyzed by liquid chromatography to determine the conversion rate and product selectivity of halobenzenes.

[0082] Figure 8 The TOF values ​​of the catalysts prepared in Examples 1-4 are shown, among which the catalyst with a theoretical Pd loading of 0.5 wt.% exhibits the best turnover frequency.

[0083] Depend on Figure 9As can be seen, copper-doped carbon nitride does not possess catalytic ability for the Suzuki coupling reaction without palladium loading. After palladium loading, Pd(0.5 wt.%) / CuCN-DMSO exhibits stronger catalytic performance than Pd(0.5 wt.%) / CuBCN and Pd(0.5 wt.%) / CuCN-H2O due to its larger specific surface area and stronger light absorption capacity, as mentioned above. In the reaction system of iodobenzene and phenylboronic acid, the yield of biphenyl is close to 100% within two hours, and its selectivity is also close to 100%. This indicates that Pd(0.5 wt.%) / CuCN-DMSO has extremely high photocatalytic ability for Suzuki coupling and has good application potential.

[0084] Figure 10 The catalytic performance of the catalyst prepared in Example 1 on different substrates is demonstrated. As shown in the figure, the catalyst exhibits high catalytic activity for various commonly used substrates, including different halobenzenes, halobenzenes with different substituents, and phenylboronic acid with different substituents, proving its high efficiency and versatility in catalyzing the Suzuki coupling reaction and demonstrating good prospects for industrial application.

[0085] Application Example 2

[0086] The cycle performance test of the catalyst prepared in this invention is conducted using the following experimental steps:

[0087] 1) First cycle: 3.0 mmol iodobenzene, 3.6 mmol phenylboronic acid, 7.2 mmol anhydrous potassium carbonate and 18 mg catalyst were dispersed in a quartz reaction tube containing 24 mL solvent (12 mL water + 12 mL ethanol) to form a suspension.

[0088] 2) A 300 W Xe lamp was used as the light source, providing visible light with a wavelength range mainly between 400-800 nm. The maximum light power density irradiating the surface of the reaction solution was 200 mW·cm². −2 To carry out photocatalytic reactions.

[0089] 3) After the reaction, the product was extracted with dichloromethane and centrifuged to remove the catalyst. The remaining reactants and products were quantitatively analyzed by liquid chromatography to determine the conversion rate and product selectivity of the halobenzene.

[0090] 4) Collect the catalyst removed by centrifugation, wash and dry it, and weigh it again. Based on the amount of remaining catalyst, weigh the amount of each substance in the reaction system in the same proportion, and carry out the next cycle. Repeat this process.

[0091] Depend on Figure 11 As can be seen, after seven cycles of photocatalytic reactions involving recycling and reuse, the catalyst prepared in Example 1 showed almost no change in activity and selectivity, indicating that the catalyst of the present invention has extremely high stability.

[0092] Application Example 3

[0093] The experimental procedures for the various catalytic composite films prepared in this invention in the photocatalytic Suzuki coupling reaction are as follows:

[0094] 1) Disperse 3.0 mmol of halobenzene, 3.6 mmol of phenylboronic acid or phenylboronic acid derivative, and 7.2 mmol of anhydrous potassium carbonate in a reaction vessel containing 24 mL of solvent (12 mL of water + 12 mL of ethanol), and place a catalytic composite membrane with dimensions of 4 cm * 4 cm in the reaction solution.

[0095] 2) A 300 W Xe lamp was used as the light source, providing visible light with a wavelength range mainly between 400-800 nm. The maximum light power density irradiating the surface of the reaction solution was 200 mW·cm². −2 To carry out photocatalytic reactions.

[0096] 3) After the reaction, the remaining reactants and products were extracted with dichloromethane, and the remaining reactants and products were quantitatively analyzed by liquid chromatography to determine the conversion rate and selectivity.

[0097] Figure 12 The paper presents a comparison of the catalytic performance of the catalytic composite membranes prepared in Examples 1, 5, and 6 during 10 cycles of reaction. The composite membrane with a thickness of 100 μm showed the highest catalytic efficiency in the first 6 cycles, but a significant decrease in catalytic efficiency occurred within 10 cycles. Figure 13 The states of the three composite membranes after cycling were shown. It was found that the 100 μm thick composite membrane was structurally destroyed under stirring shear force due to its lower mechanical properties, while the 200 μm and 300 μm thick composite membranes maintained their intact structures after 10 cycles. However, due to the shielding effect of the PVDF substrate, the 300 μm thick membrane exhibited lower catalytic efficiency. Therefore, considering both stability and catalytic efficiency, this invention selected 200 μm as the optimal thickness for the catalytic composite membrane.

[0098] Application Example 4

[0099] The comparative test of the cycle performance of the catalyst and the catalytic composite membrane prepared in this invention is conducted, and the experimental steps are as follows:

[0100] 1) First cycle of powdered catalyst: 3.0 mmol iodobenzene, 3.6 mmol phenylboronic acid, 7.2 mmol anhydrous potassium carbonate and 4.7 mg catalyst were dispersed in a quartz reaction tube containing 24 mL solvent (12 mL water + 12 mL ethanol) to form a suspension.

[0101] 2) Membrane reaction cycle: 3.0 mmol iodobenzene, 3.6 mmol phenylboronic acid, and 7.2 mmol anhydrous potassium carbonate were dispersed in a reaction vessel containing 24 mL of solvent (12 mL water + 12 mL ethanol). A catalytic composite membrane with dimensions of 4 cm * 4 cm was placed in the reaction solution.

[0102] 3) A 300 W Xe lamp was used as the light source, providing visible light with a wavelength range mainly between 400-800 nm. The maximum light power density irradiating the surface of the reaction solution was 200 mW·cm². −2 To carry out photocatalytic reactions.

[0103] 4) After the reaction, the remaining reactants and products are extracted with dichloromethane. The powdered catalyst is collected by centrifugation, washed, and directly added to the next photocatalytic reaction without considering weight loss. The catalytic composite membrane is soaked and washed with water and ethanol solution and then directly carried out the next photocatalytic reaction.

[0104] 5) Use liquid chromatography to analyze the remaining reactants and products to determine the conversion rate and selectivity.

[0105] like Figure 14 As shown, the cycling test results of the powder catalyst and the catalytic composite membrane prepared in Example 1 indicate that the product selectivity of all cyclic reactions is close to 100%. Although the initial catalytic activity of the catalytic composite membrane is slightly lower than that of the powder catalyst, its cycling stability is significantly better, and its catalytic performance advantage gradually becomes more prominent with the increase of cycling cycles. Powder catalysts are prone to mass loss during separation and recovery; while the catalytic composite membrane can anchor the active components in the membrane substrate, effectively preventing catalyst detachment, thus exhibiting excellent long-term cycling stability. The composite membrane overcomes the practical application bottlenecks such as the difficulty in separating powder catalysts and the complexity of the recovery process, greatly enhancing the industrial application potential of catalysts and possessing good practical value.

[0106] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.

Claims

1. A highly efficient and recyclable Suzuki coupling reaction photocatalyst, characterized in that, The photocatalyst is a composite structure in which palladium clusters are supported on copper single-atom-doped flower-shaped hollow spherical graphitic carbon nitride. The copper single-atom-doped flower-shaped hollow spherical graphitic carbon nitride is prepared by supramolecular self-assembly combined with high-temperature calcination using melamine and cyanuric acid as precursors in a dimethyl sulfoxide solvent system, and has a flower-shaped hollow spherical multi-level structure. The palladium clusters are directionally loaded onto copper single-atom active sites by photodeposition to achieve electronic structure modulation and adapt to the photocatalytic Suzuki coupling reaction.

2. The high-efficiency, recyclable Suzuki coupling reaction photocatalyst according to claim 1, characterized in that, The photocatalyst contains 0.1–2.0 wt.% palladium.

3. A catalytic composite membrane based on the photocatalyst according to any one of claims 1 to 2, characterized in that, The catalytic composite membrane uses polyvinylidene fluoride as the matrix, with the photocatalyst doped and dispersed, and polyvinylpyrrolidone added as a film-forming aid. The catalytic composite membrane is prepared by a non-solvent-induced phase separation method, and has a macroscopic membrane structure that can be directly clamped, separated and recovered.

4. The catalytic composite membrane according to claim 3, characterized in that, The thickness of the catalytic composite membrane is 100–400 μm, and the membrane area can be adjusted as needed.

5. A method for preparing the highly efficient and recyclable Suzuki coupling reaction photocatalyst according to any one of claims 1 to 2, characterized in that, Includes the following steps: 1) Preparation of copper-doped flower-shaped hollow spherical graphitic carbon nitride support CuCN-DMSO: Melamine and copper-containing raw materials were dissolved sequentially in dimethyl sulfoxide and stirred at room temperature to obtain a homogeneous mixed solution; cyanuric acid was dissolved in dimethyl sulfoxide to obtain a homogeneous solution; the two solutions were mixed and supramolecular self-assembled to obtain a suspension, which was then stirred at room temperature, centrifuged, dried, ground, calcined at high temperature under an inert atmosphere, and cooled to obtain the CuCN-DMSO support; 2) Preparation of catalyst by photodeposition of supported palladium: CuCN-DMSO support was dispersed in a pure water system, ultrasonically dispersed and then a soluble palladium salt solution was added. The mixture was pretreated by stirring under dark conditions, and then palladium clusters were deposited by photodeposition. After centrifugation, washing and vacuum drying, Pd / CuCN-DMSO photocatalyst was obtained.

6. The method for preparing the photocatalyst according to claim 5, characterized in that, In step 1), the mass ratio of melamine to dimethyl sulfoxide is 1–10:200, the mass ratio of cyanuric acid to dimethyl sulfoxide is 1–10:200, and the concentration of copper in the mixed solution is 0.258–2.58 g·L⁻¹. -1 The calcination temperature is 500–600 °C, the calcination time is 3–5 h, and the calcination atmosphere is nitrogen; in step 2), the mass ratio of CuCN-DMSO to water is 0.5–2:1000, and the palladium concentration in the palladium salt solution is 0.532–2.128 g·L⁻¹. -1 The dark stirring time is 1–4 h, and the light deposition time is 0.5–2 h.

7. A method for preparing the catalytic composite membrane according to any one of claims 3 to 4, characterized in that, The process includes the following steps: dispersing the Pd / CuCN-DMSO photocatalyst prepared according to any one of claims 5 to 6 in N,N-dimethylformamide, and ultrasonically dispersing it uniformly to obtain a catalyst suspension; adding polyvinylidene fluoride and polyvinylpyrrolidone to the suspension, and stirring at a constant temperature of 55–85 °C for 2–8 h to prepare a uniform casting solution; uniformly coating the casting solution onto the surface of a substrate, and curing it into a film by a non-solvent-induced phase separation method to obtain a Pd / CuCN-DMSO@PVDF catalytic composite film.

8. The method for preparing the catalytic composite membrane according to claim 7, characterized in that, The mass ratio of polyvinylidene fluoride, polyvinylpyrrolidone, N,N-dimethylformamide, and Pd / CuCN-DMSO photocatalyst in the casting solution is 34:10:189.6-303.4:2-12; the polyvinylpyrrolidone is of type K88-96.

9. An application characterized in that, The photocatalyst according to any one of claims 1 to 2 and the catalytic composite membrane according to any one of claims 3 to 4 are applied to the photocatalytic Suzuki coupling reaction.

10. The application according to claim 9, characterized in that, The substrates for the Suzuki coupling reaction include halogenated benzenes with different substituents and substituted phenylboronic acid derivatives. The reaction is carried out under ambient temperature and light conditions, and the photocatalyst and catalytic composite membrane can be recycled and reused multiple times.